Solving a Production and Inventory Model with a Minimum Lot Size Constrain - Knut Richter; Irena Okhrin (European University Viadrina, Department of Business Administration and Economics, 2007)
The paper deals with the analysis of a special dynamic production and inventory model. In this model logical restrictions to fulfill an accepted constant minimal level of the production lot size are incorporated, instead of keeping setup cost in the objective function, as it is common in many other models. Detailed optimality conditions are derived, which make possible the application of a simple dynamic programming recursion procedure.
Keywords: 330; dynamic production-inventory model; minimum lot size; dynamic programming; Produktionsplanung; Losgros̈se; Lagerhaltungsmodell; Dynamische Optimierung; Theorie